Implementasi Metode Pembelajaran Berbasis Diskusi Kelompok dalam Membentuk Keaktifan Siswa di SD MusaTanggulangin Sidoarjo - Mita Yolanda TR; Muhamad Yusron Maulana El-Yunusi (Jurnal Dirosah Islamiyah, 2025)
A conducive classroom atmosphere with an optimal learning process can be formed if students are active in participating in learning. The aim of writing this article is to create activeness in grade 4 students at Musa Elementary School by implementing group discussion-based learning methods. The research method used is a descriptive qualitative approach. The results of the research show that the group discussion-based learning method that has been implemented at Musa Elementary School has proven to be effective in building student activity. This is evidenced by the change, from when students initially looked bored during the learning process, now students actively participate in discussions. Apart from that, students are also able to think critically if given a problem. They are responsive in solving these problems. In conclusion, the learning method applied is very effective.